Analisis rasio lancar Pt Astra Agro Lestari TBK periode 2019-2023 : seberapa likuid perusahaan? - Frasasti, Meilinda (Maliki Interdisciplinary Journal, 2025)
Analysis of financial statements in each company is very necessary. Analyzing financial statements can be seen in the liquidity ratio. There are three types of liquidity ratios, one of which is the current ratio used in this study. This study aims to find out how liquid the company is in maintaining the stability of its current ratio. Companies participating in the Indonesia Stock Exchange (IDX) are the subject of this study in 2019-2023. According, the results of the research, means that the company is able to pay its short-term obligations of PT Astra Agro Lestari Tbk has a value of > 1, which means that the company is able to pay off its short-term obligations. In the next research, it is expected to use other ratios and compare them with other companies in order to improve a more effective strategy.